2021
DOI: 10.1021/acsomega.1c04826
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experimental Conditions with Machine Learning for Collaborative Organic Synthesis Reactions Using Transition-Metal Catalysts

Abstract: To improve product yields in synthetic reactions, it is important to use appropriate catalysts. In this study, we used machine learning to design catalysts for a reaction system in which both Buchwald−Hartwig-type and Suzuki−Miyaura-type cross-coupling reactions proceed simultaneously. First, using an existing dataset, yield prediction models were constructed with machine learning between experimental conditions, including the substrate and catalyst and the yields of the two products. Seven methods for calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The vast amount of chemical data generated during wet-lab experiments is often underutilized. The application of data-driven approaches for reaction discovery, optimization, and prediction can make a significant impact on efficient exploration of the multidimensional chemical space . In recent years, the increase in computing power ably complemented by improved data availability has led to notable progress in the use of machine learning (ML) in many areas of chemistry, ranging from retrosynthetic planning to property or reaction outcome predictions …”
Section: Introductionmentioning
confidence: 99%
“…The vast amount of chemical data generated during wet-lab experiments is often underutilized. The application of data-driven approaches for reaction discovery, optimization, and prediction can make a significant impact on efficient exploration of the multidimensional chemical space . In recent years, the increase in computing power ably complemented by improved data availability has led to notable progress in the use of machine learning (ML) in many areas of chemistry, ranging from retrosynthetic planning to property or reaction outcome predictions …”
Section: Introductionmentioning
confidence: 99%
“…Studies on selectivity 10 and machine learning investigations of the selectivity in multiple coupling reactions have been reported. 11 Although the maximum yield of BHCC reaction products was less than 10% when aryl chlorides were used in the reaction system where BHCC and SMCC reactions occurred simultaneously, a catalyst with a 33% yield of BHCC products was successfully developed. 11 The objective of this study was to develop catalyst−ligand combinations, including the development of new variables (x) under all experimental conditions, an estimation of the reaction mechanism, and new reaction developments.…”
Section: Introductionmentioning
confidence: 99%
“…Although the detailed reaction mechanism in the reaction system where BHCC and SMCC reactions occur simultaneously is not fully understood, the same reaction mechanism can be estimated up to oxidative addition in BHCC and SMCC cross-coupling reactions. Studies on selectivity and machine learning investigations of the selectivity in multiple coupling reactions have been reported . Although the maximum yield of BHCC reaction products was less than 10% when aryl chlorides were used in the reaction system where BHCC and SMCC reactions occurred simultaneously, a catalyst with a 33% yield of BHCC products was successfully developed …”
Section: Introductionmentioning
confidence: 99%
“…11,12 For example, a cross-coupling reaction was optimized in terms of concentrations and catalysts with a small number of synthetic data. 13 Recently, Tamura et al demonstrated the optimization of material properties using molecular descriptors and the experimentally obtained analytical data. 14 Also, the solubility data were also predicted with a combination of analytical data and molecular descriptors.…”
Section: Introductionmentioning
confidence: 99%